2020
DOI: 10.1177/2380084420981882
|View full text |Cite
|
Sign up to set email alerts
|

The Queensland Birth Cohort Study for Early Childhood Caries: Results at 7 Years

Abstract: Aims: This study investigated caries predictors in 378 children remaining from a birth cohort of 1,052 at 7 y and compared the efficacy of home visits (HVs) and telephone contacts (TCs) for early childhood caries (ECC) prevention. Methods: The HVs or TCs were made at ages 6, 12, 18, 30, and 42 mo with annual dental clinic examinations at ages 2 to 7 y. At every visit, the parents completed validated questionnaires regarding the children’s family, medical, dental, and dietary histories. Results: The caries prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…In older adults, the main reason for accessing DDC services were disability [5,7,[32][33][34], limited income [5,32,34], and older people with cognitive problems such as Alzheimer's patients [33]. In early childhood, caries have been reported to be strongly correlated with low socioeconomic status [35] and limited access to early preventive dental issues [36]. Some research has confirmed that patients who choose DDC programs have much better health than those who do not [32,37].…”
Section: Advancement Of Ddcmentioning
confidence: 99%
See 1 more Smart Citation
“…In older adults, the main reason for accessing DDC services were disability [5,7,[32][33][34], limited income [5,32,34], and older people with cognitive problems such as Alzheimer's patients [33]. In early childhood, caries have been reported to be strongly correlated with low socioeconomic status [35] and limited access to early preventive dental issues [36]. Some research has confirmed that patients who choose DDC programs have much better health than those who do not [32,37].…”
Section: Advancement Of Ddcmentioning
confidence: 99%
“…Patients who preferred regular DDC services were able to maintain several healthy tooth roots [33]. DDC has also been reported to be effective in maintaining dental health in children, especially in reducing Early Childhood Caries (ECC) compared to telephone contacts [35]. However, DDC also has some disadvantages.…”
Section: Advantages and Disadvantages Of Ddc Servicesmentioning
confidence: 99%
“… 4 The worldwide prevalence of hypomineralized EDs of the primary molars has been reported to range from 0% to 41% at the individual level with a pooled prevalence of 7%, and ranged from 0% to 30% at the tooth level, with a pooled prevalence of 4%. 5 The occurrence of dental EDs, particularly demarcated opacities, has been reported to be associated with an increased risk of caries in permanent and primary teeth 6 , 7 , 8 , 9 , 10 , 11 , 12 and findings from a few studies suggest that hypomineralized EDs might predispose teeth to a more rapid progression of caries, thus leading to poorer carious outcomes where access to care may be limited. 7 , 8 Also, hypomineralized EDs of second primary molars have been reported to be associated with poorer oral health‐related quality of life.…”
Section: Introductionmentioning
confidence: 99%